Risk Factors for Hemorrhagic Stroke in Patients Admitted to the Emergency Department: A Retrospective Cross-sectional Study - Mandana Pouladzadeh; Hesam Hoveizavi; Mofid Hosseinzadeh (Biomedical and Biotechnology Research Journal, 2025)
Background: Hemorrhagic strokes accounting for 10%–20% of all strokes. This study aims to assess the medical and laboratory profiles of patients with hemorrhagic stroke to identify risk factors and predictors of mortality. Methods: In this retrospective study, the complete medical records of patients with hemorrhagic stroke who were referred to the emergency department of the hospital in 2022 were reviewed. Demographic information (age and sex), clinical data, and laboratory findings on the day of admission were collected for statistical analyses. Results: A total of 285 patients with hemorrhagic stroke were evaluated, comprising 190 males and 95 females. The mean age of men was significantly higher than women (P = 0.001). Moreover, the disease incidence was notably higher in men and among patients aged 60 years and older (P = 0.0001). The most common comorbidities included hypertension (70.2%), diabetes (36.1%), inactivity (35.1%), and cardiac ischemia (31.2%). Anemia, defined by abnormally low hemoglobin levels, was present in 76.5% of patients and correlated with the incidence of hemorrhagic stroke (P = 0.0001). In addition, 89.47% of patients had hyperglycemia, which was also associated with hemorrhagic stroke (P = 0.0001). However, other biomarkers showed no significant correlation (P > 0.05). Notably, thrombocytopenia was significantly linked to a higher risk of death (hazard ratio [95% confidence interval CI]: 0.998 [0.996–1], P = 0.03). Conclusion: Male sex, older age, comorbidities, previous stroke, anemia, hyperglycemia, and thrombocytopenia are identified as risk factors for hemorrhagic stroke. Furthermore, thrombocytopenia seems to be associated with high risk of death in these patients, underscoring the need for its timely treatment.